2017
DOI: 10.1097/gme.0000000000000762
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic exercise training on ACE and ADRB2 gene expression, plasma angiotensin II level, and flow-mediated dilation: a study on obese postmenopausal women with prehypertension

Abstract: Ten weeks of MIET modulates ACE and ADRB2 gene expression, decreases Ang II plasma levels, and improves endothelial function in obese PMW, and these alterations are associated with reduction in BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
45
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 50 publications
1
45
0
1
Order By: Relevance
“…6 In other words, aerobic exercise-induced cardiovascular system adaptations can be accompanied by a better quality of life and decreased cardiovascular diseases in sedentary post-menopausal women. 3,9 In addition, moderate-intensity aerobic exercise provides changes in the heart that contribute to the greater peak Q and aerobic capacity. Changes in cardiac dimensions and blood volume play the primary role in enhancing SV, and hence Q.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…6 In other words, aerobic exercise-induced cardiovascular system adaptations can be accompanied by a better quality of life and decreased cardiovascular diseases in sedentary post-menopausal women. 3,9 In addition, moderate-intensity aerobic exercise provides changes in the heart that contribute to the greater peak Q and aerobic capacity. Changes in cardiac dimensions and blood volume play the primary role in enhancing SV, and hence Q.…”
Section: Discussionmentioning
confidence: 99%
“…9 In another study, we reported that the aerobic exercise training created a suitable level of fitness, thereby can affect the aging process. 3,9,10 In other words, moderateintensity aerobic exercise is one of the most effective ways of reducing risk factors for cardiovascular disease and mortality. 9,10 Thus, the first purpose of this study was to examine the effect of 12 weeks of the protocol; warm up-walking and jogging moderate-intensity aerobic exercise programrecovery (W-WJMIAEP-R) on ECG indices, including heart rate, cardiac waves, and cardiac segments & intervals in post-menopausal women.…”
mentioning
confidence: 97%
See 3 more Smart Citations